Peanut cultivars display susceptibility by triggering outbreaks of Tetranychus ogmophallos (Acari: Tetranychidae) - Melville, Cirano Cruz [UNESP]; Zampa, Samuel Felipe [UNESP]; Savi, Patrice Jacob [UNESP]; Michelotto, Marcos Doniseti; Andrade, Daniel Junior [UNESP] (Springer Nature, 2019)
The peanut red spider mite, Tetranychus ogmophallos Ferreira and Flechtmann (Acari: Tetranychidae), is an important pest of peanut in Brazil and is considered a quarantine pest in other countries. This study investigates the development, reproduction, survival and life table parameters of T. ogmophallos on five peanut cultivars—three with high levels of oleic acid [high oleic] and recently released: Granoleico, IAC OL 3 and IAC 503; and two regular and previously used by farmers: Runner IAC 886, IAC Tatu ST 3—and two breeding lines (L. 8008 and L. 322) in the growth chamber. There were differences between the developmental times of all immature stages, the oviposition period, fecundity and adult longevity of T. ogmophallos reared on the peanut cultivars and breeding lines. The longest duration of the immature stage and lowest fecundity occurred on cultivars Granoleico and Runner IAC 886, and breeding line L. 322, which also displayed the lowest intrinsic rate of increase (r), finite rate of increase (λ) and net reproductive rate (R0) and the shortest mean generation time (T). The highest fitness occurred on the IAC Tatu ST, IAC OL 3, IAC 503 and L. 8008. Our study shows that peanut cultivars belonging to the group with high oleic trait and recently released (IAC OL 3 and IAC 503) are susceptible to T. ogmophallos, except Granoleico, which is resistant. The regular and previously used cultivar Runner IAC 886 and breeding line L. 322 are resistant to the peanut red spider mite.
Keywords: Age-stage two-sex life table; Arachis hypogaea; Demographic parameters; Peanut red spider mite